ANALISIS RASIO LIKUIDITAS, RASIO SOLVABILITAS, DAN UNDERWRITING RATIO UNTUK MENGUKUR KINERJA KEUANGAN PT MANDIRI AXA GENERAL INSURANCE DI INDONESIA PASCA OJK (OTORITAS JASA KEUANGAN ) - Widiati, Putri Kurnia; Aisyah, Esy Nur (Fakultas Ekonomi, UIN Maliki Malang, 2013)
This study aimstoanalyzethe development ofthe financial performance of PT Mandiri AXAGeneralInsurance in Indonesia after the establishment of the FSA (Financial Services Authority) in 2013 by using theanalysis of liquidity ratios, solvency ratios using solvabillitas rate calculation and risk-based minimum capital,and undderwiting ratio. Based on the results it can be concluded that penellitian seen from the calculation ofthe solvency ratiousing solvabillitas level of risk-based andminimum capital ratio under wrting result andshowed unfavorable results, while the liquidity ratio has increase devery year. The results of the calculationof this ratio in dicates poor performance (except for the liquidity ratio) associated with the presence of FSA(Financial Services Authority).